Perceived Value of Preadmission Physical Therapy Observation Hours and Their Ability to Predict Academic Performance. Issue 1 (March 2018) - Wheeler, Emma; Finucane, Sheryl; Soper, Shawne; Mayhew, Thomas
Abstract : Introduction: Most physical therapist (PT) and physical therapist assistant (PTA) education programs require applicants to complete observation hours (ObHr) before admission. Observation hours are believed to enable the prospective PT and PTA student to gain knowledge about the profession and increase chances of success in academic programs; however, few studies have examined these relationships. The purposes of this study were to: 1) examine the relationship between the number of ObHr completed and indicators of success in a Doctor of Physical Therapy (DPT) program, 2) identify PT and PTA student opinions and perceived value of the required ObHr, including the number of hours needed to make an informed decision to pursue physical therapy as a career, and 3) identify clinical instructor (CI) opinions about the perceived value of ObHr and their impact on clinic productivity. Methods: Part 1 was a retrospective cohort study, examining data from 323 students who matriculated into a DPT program during a 6-year period (2009–2014). The relationship between admission variables (undergraduate grade point average [GPA], undergraduate math/science GPA, verbal Graduate Record Examination [GRE], quantitative GRE, age, and total ObHr) and outcome variables (National Physical Therapy Examination [NPTE] success, DPT probation status, and DPT GPA) were examined. Parts 2 and 3 focused on perceived value of ObHr gathered from surveys of PT and PTA students and CIs. Results: The number of ObHr was not a significant predictor of NPTE success, DPT probation status, or DPT GPA. Most PT (92%) and PTA (83%) students believed that ObHr positively impacted their decision to pursue physical therapy as a profession and that they needed 40–60 hours to make this decision. Most CIs (64%) do not believe that reducing ObHr opportunities would result in an increase in the number of full-time clinical experiences offered by their clinic. An overwhelming majority of the CIs (95%) believed that ObHr are meaningful for prospective students. Discussion and Conclusion: Observation hours were perceived as being valuable by both PT and PTA students and CIs. Observation hours may be useful to prospective PT students to help determine whether they pursue a career in physical therapy. However, there is no evidence that ObHr impact DPT academic performance. Physical therapist students may need fewer ObHr to confirm a career choice than what some programs currently require. Abstract : Supplemental Digital Content is Available in the Text.